CHARACTERIZATION OF POLYMORPHS, SALT AND COCRYSTAL OF MEFENAMIC ACID IN AN EFFORT TO IMPROVE SOLUBILITY - Ishariyanto, Riski
Mefenamic acid (AM) based on the Biopharmaceutical Classification System (BCS) is included in class II drugs, which have low solubility and high permeability so that the bioavailability of the drug is limited. This study aims to characterized the polymorphs, salt and cocrystal of AM in an effort to improve its solubility and dissolution. AM has two polymorphs, namely form I (AM-I) and form II (AM-II). AM-I was obtained from the recrystallization of AM with dimethylformamide (DMF) solvent while AM-II is a raw material for mefenamic acid. The salt (Na-M) was obtained from the chemical reaction between AM and NaOH in ethanol p.a solvent with a molar ratio of 1:1. Cocrystal (AM-FUM) were prepared using the slurry method between AM and fumaric acid (FUM) in ethanol p.a solvent with a molar ratio of 1:1. AM-I, AM-II, Na-M and AM-FUM were characterized by hot stage microscope (HSM), powder x-ray diffraction (PXRD), fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and scanning electron microscope (SEM). The HSM results of AM showed an enantiotropy system, namely the change in form of AM-II to AM-I which melts at 188 and 215°C, this is supported by DSC data which has two endothermic peaks at 226,63 and 232,25°C. The AM-I habit has a plate shape while AM-II, Na-M and AM-FUM have a rectangular shape. Na-M based on DSC results has a melting point at 250,70°C and AM-FUM at 220,14°C. In 0,01 N NaOH solvent AM-I and AM-II have almost the same solubility of 2,145 and 2,156 mg/mL while Na-M has a higher solubility of 24,66 mg/mL and AM-FUM have a solubility of 1,518 mg/mL. The dissolution profiles of AM-I, AM-II, Na-M and AM-FUM showed that after five minutes Na-M had the highest %dissolution of 74,39 while AM-I of 12.57, AM-II of 1.73 and AM-FUM of 3.95. Based on the results of the research, it can be concluded that Na-M has higher solubility and %dissolution compared to AM-I, AM-II, and AM-FUM.